2023
DOI: 10.1111/anae.16001
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative mortality and complications in patients with and without pre‐operative SARS‐CoV‐2 infection: a service evaluation of 24 million linked records using OpenSAFELY

Abstract: Surgical decision-making after SARS-CoV-2 infection is influenced by the presence of comorbidity, infection severity and whether the surgical problem is time-sensitive. Contemporary surgical policy to delay surgery is informed by highly heterogeneous country-specific guidance. We evaluated surgical provision in England during the COVID-19 pandemic to assess real-world practice and whether deferral remains necessary. Using the OpenSAFELY platform, we adapted the COVIDSurg protocol for a service evaluation of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Indeed, a blanket ban has never been recommended [4,9], but there are some concerns that previous guidance has been interpreted in this manner. From a population perspective, recent data indicate that the absolute risk of surgery soon after SARS-CoV-2 infection might be lower in the UK than previously reported by COVIDSurg [3,20].…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Indeed, a blanket ban has never been recommended [4,9], but there are some concerns that previous guidance has been interpreted in this manner. From a population perspective, recent data indicate that the absolute risk of surgery soon after SARS-CoV-2 infection might be lower in the UK than previously reported by COVIDSurg [3,20].…”
Section: Discussionmentioning
confidence: 79%
“…More recent data have suggested that risks associated with surgery within 7 weeks of infection may be more modest than in previous phases of the pandemic [18,20]. In the Omicron post-vaccination era, a population-based data platform analysis in England showed that surgery 2 weeks, 2-4 weeks, 4-7 weeks and > 7 weeks after SARS-CoV-2 infection was associated with a 30-day mortality rate of 1.1%, 0.5%, 0.3% and 0.2%, respectively [20]. Compared with equivalent data from the first year of the pandemic (i.e.…”
Section: Timing Of Elective Surgery After Sars-cov-2 Infectionmentioning
confidence: 99%
See 3 more Smart Citations